Crisis, Industrial Revolutions and Economic Methodology - Prodanov, Hristo (Research Papers, 2023)
The object of the study is the economic methodology, and the subject is the change in it at the different stages of technological development. The goal is to reveal the reasons for this change, and the task is to justify the need for a new revision in the methodology given the next technological stage related to the Fourth Industrial Revolution. A historical approach is applied, through which an attempt is made to reveal the historical change in economic methodology, and then a systemic approach, which aims to reveal the causal relationship between crises, industrial revolutions and changes in economic reality, leading at each subsequent stage to changes in the methodology of economic science and to new economic paradigms. This approach determines the structure of the study, which investigates the changes in economic methodologies at the pre-industrial stage and then during the different industrial revolutions leading to the emergence of different economic methodologies and theories. The conclusion is that, in the midst of the Fourth Industrial Revolution, we are observing changes in economic reality that can hardly be described, understood, predicted through the existing methodologies and the theories behind them, which necessitates a new rethinking of the economic methodology. The study is the first large-scale attempt in our country to analyze these processes and sets important lines of thinking in this regard.